Imobilização de lipase em nanotubos de carbono - Fagner Ferreira Pinto (2008)
The enzyme immobilization is a process that it searches to add quality to the enzymatic catalysis increasing the efficiency, stability, resilience and making possible one future to reuse the enzymes. The use of new processes of immobilization is recent subject of some works and currently new enzymatic supports have being bred and tested for the most varied goals. The carbon nanotubes are a new alternative that have being tested for many researchers for enzyme immobilization with promising results, had its notables properties as raised relation area/volume, high mechanics resistance and possibility of being used in hydrophobic or hydrophilic substrata. Lipases are enzymes that possess pair function, possessing lipolitic activity in hydrophilic substrata and esterase in hydrophobic environments had its versatility widely they are used in diverse sectors of the industry. Candida rugosa type VII lipase was immobilized in sodium alginate, single-walled carbon nanotubes (SWNT) and of multi-walled carbon nanotubes (MWNT) and the results had been analyzed. From the gotten results the enzyme can be concluded that the immobilization of lipase in MWNT is presented as a promising alternative, therefore continues active after the process of immobilization with 22% of its preserved activity.